Combined antihypertensive in patients with high risk of cardiovascular events - Yu. A. Karpov (Кардиоваскулярная терапия и профилактика, 2009)
The article is devoted to the issue of optimizing blood pressure control in the patients with Type 2 diabetes mellitus, with or without arterial hypertension, by antihypertensive therapy with a fixed combination of low doses of perindopril and indapamide. Such therapeutic approach is consistent with the basic principles of cardiovascular risk stratification and facilitates prognosis improvement.